Droplet microfluidic technologies for next-generation high-throughput screening - Ali, Mushtaq; Kim, Woohyuk; Park, Jinsoo (Frontiers in Lab on a Chip Technologies, 2023)
Droplet microfluidics has evolved into a promising platform for high-throughput screening (HTS), allowing for rapid and precise analysis of thousands of samples encapsulated within droplets. Droplet microfluidic platform offers versatility, high-throughput, and the ability to compartmentalize reactions for a wide range of applications including pharmaceutics, cell analysis, and combinatorial chemical analysis. While droplet-based microfluidics has made considerable advances in automating basic laboratory tasks, for instance, manipulation, storage, and analysis, there has been comparatively little advancement toward HTS applications. The complexity of the technology, the lack of standardization, and the challenges associated with screening large numbers of samples are all factors that have contributed to the limited adoption of droplet-based microfluidics in HTS. In this perspective, we provide a comprehensive overview of the progress of droplet microfluidics as a potential platform for next-generation HTS, specifically in the domain of droplet separation and library generation. We hope that this perspective will inspire further research in relevant academic fields and contribute to the development of innovative HTS strategies based on droplet microfluidic technologies.